Evolutionary and Expression Analyses Show Co-option of khdrbs Genes for Origin of Vertebrate Brain - Wang, Su; Yang, Qingyun; Wang, Ziyue; Feng, Shuoqi; Li, Hongyan; Ji, Dongrui; Zhang, Shicui (Frontiers in Genetics, 2018)
Genes generated by whole genome duplications (WGD) can be co-opted by changing their regulation process or altering their coding proteins, which has been shown contributable to the emergence of vertebrate morphological novelties such as vertebrate cartilage. Mouse khdrbs genes, differing from its invertebrate orthologs, were mainly expressed in brain, hinting that khdrbs gene family as a member of genetic toolkit may be linked to vertebrate brain development. However, the evolutionary relationship between khdrbs gene family and vertebrate brain development is unclear. First, we analyzed the evolutionary history of khdrbs gene family in metazoans, and then investigated their expression patterns during early development and in adulthood of zebrafish. We found that the duplication of khdrbs gene family by WGD took place in zebrafish, and all zebrafish khdrbs genes were predominantly expressed in the substructures of brain during early development. Given the expression of invertebrate khdrbs gene in germ line, the distinct expression domains of zebrafish khdrbs genes in brain suggested that the duplicated khdrbs genes are co-opted for promoting the evolutionary origin of vertebrate brain.